2018
DOI: 10.1016/j.jaci.2017.04.045
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 stimulates adaptive IL-22 production and promotes allergic contact dermatitis

Abstract: Background Atopic dermatitis (AD) and allergic contact dermatitis (ACD) are both forms of eczema and are common inflammatory skin diseases with a central role of Th22-derived IL-22 in their pathogenesis. Although prostaglandin E2 (PGE2) is known to promote inflammation, little is known about its role in processes related to AD and ACD development, including IL-22 up-regulation. Objectives To investigate whether PGE2 has a role in IL-22 induction and development of ACD, which has increased prevalence in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 55 publications
(94 reference statements)
0
33
0
Order By: Relevance
“…Our results showed that AdMSCs prevented AD from increasing the serum PGE2 level. The prostaglandin PGE2 can induce IL-22 from T cells through its receptors such as the prostanoid receptors EP2 and EP4 ( Robb et al, 2018 ). Selective deletion of EP4 in T cells limits atopic-like skin inflammation ( Robb et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that AdMSCs prevented AD from increasing the serum PGE2 level. The prostaglandin PGE2 can induce IL-22 from T cells through its receptors such as the prostanoid receptors EP2 and EP4 ( Robb et al, 2018 ). Selective deletion of EP4 in T cells limits atopic-like skin inflammation ( Robb et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, epigenetic changes in the PTGER4 gene enhancer in Th17 cells were also found to be associated with human autoimmune diseases such as MS, CD and allergy (Farh et al ., ). Consistent with these GWAS findings, the expression of PGE 2 signalling pathway genes (including both PGE 2 synthases and receptors) was found to be positively correlated with IL‐23/Th17 signature genes as well as disease severity in biopsy samples of human inflamed tissues with various chronic inflammatory conditions such as MS, CD, psoriasis and atopic dermatitis (Lee et al ., ; Robb et al ., ; and unpublished observations). Collectively, these genetic and epigenetic studies revealed conserved associations of variants in the PGE 2 ‐EP 4 signalling pathway with various IL‐23/Th17‐dependent human chronic autoimmune diseases.…”
Section: Pg‐cytokine Crosstalk In Immune and Allergic Inflammationmentioning
confidence: 97%
“…dinitro‐fluorobenzene)‐induced generation of IL‐22 + T‐cells in vivo and attenuated chronic allergic contact dermatitis induced by repeated oxazolone challenge (Robb et al ., ). Interestingly, genes related to PGE 2 and IL‐22 pathways were coordinately up‐regulated in lesional skin from human atopic dermatitis, and their expression in inflamed skin was also down‐regulated after the administration of corticosteroid or UVB treatments (Robb et al ., ). These results suggest a crucial role for PGE 2 ‐IL‐6/IL‐23 crosstalk in the generation of IL‐22 + T‐cells and the promotion of T‐cell‐mediated chronic inflammatory skin disease.…”
Section: Pg‐cytokine Crosstalk In Immune and Allergic Inflammationmentioning
confidence: 97%
See 1 more Smart Citation
“…PGE 2 stimulates IL-17 and aryl hydrocarbon receptor signalling pathways in human and mouse T cells through EP2/EP4 receptor -cAMP-PKA signalling, necessary for generation of pathogenic Th17 cells (Boniface et al, 2009;Lee et al, 2019;Robb et al, 2018;Yao et al, 2009). Given that SARS-CoV-2 infection specifically upregulates IL-17F signalling and aryl hydrocarbon receptor signalling (Z.…”
Section: Pge 2 On T Cell Functionsmentioning
confidence: 99%